COMPARISON BETWEEN INDONESIA AND ASUTRALIA IN ADDRESSING POVERTY AND INCOME INEQUALITY DURING INDONESIA POST REFORMATION ERA 1998-2018 - Dharma, Budhi (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2024)
This article discusses the comparison of how developing and developed countries deal with poverty and income inequality. Developing country is represented by Indonesia and Australia from another side. Using systematic review as a methodology, this articles then using secondary data both qualitative and quantitative to describe and compare how both countries tackle poverty and income inequality at the same time. This article concludes that there are differences and similarities can be seen as a key factor to boost the performance of poverty alleviation at the same time. This article also argues that there are several features can be adopted to transform Indonesia’s social policy.